ANALYSIS OF THE ADOPTION RATES OF WATERMELON ENTERPRISE IN OGBA/EGBEMA/NDONI LOCAL GOVERNMENT AREA OF RIVERS STATE, NIGERIA (Singaporean Journal of Business Economics and Management, 2025)
The study was focused on the analysis of the adoption rates of watermelon in Ogba/Egbema/Ndoni Local Government Area (ONELGA) of Rivers State, Nigeria. A total of 72 respondents, selected through snowballing and simple random sampling techniques were used in the study. Data obtained were analyzed, using percentages, mean scores and t-test for test of significance. The findings showed that: Majority of the dealers of watermelon in Ogba/Egbema/Ndoni local government area adopted the marketing of the fruits much more than the production in a subsistence scale. It revealed that eighty-six percent of watermelon products, especially the fruits traded and consumed in the area were usually brought from outside the area and most of the farmers involved in watermelon enterprise in the area were middle adult women who do not acquire formal education above secondary. It further shows that the adoption rate of watermelon was low both in production and in marketing, hence the dependency on outside supply to meet the consumption needs of the consumers of watermelon in the area The major constraints to the adoption of watermelon in ONELGA were: Inadequate information about the watermelon enterprise (production, processing and marketing as well as its economic profitability), high cost of transporting the fruits from outside, lack of accessible credit facilities for farmers and the perception of watermelon enterprise by the people as a business for the poor.The t-test result showed a t-cal of (0.56) which was less than t-critical (1.69) at 0.05 significant level, which led to the acceptance of the null hypothesis, meaning that there is no significant difference between the watermelon producers and the marketers as regards the constraints to adoption of watermelon in ONELGA. The study therefore, recommended that farmers in the area including men and youths should be meaningfully encouraged through grants and soft loans to produce watermelon in commercial quantities and the Agricultural Transformation Agenda as an avenue to make credits available to farmers through the E-Wallet should be extended to ONELGA for farmers to access.